The effectiveness of the use of iron caseinate for correcting iron deficiency and hematological parameters under the experimental model of alimentary anemia in rats - Kakhanouski, Aliaksandr I.; Arol, Nataliya M.; Kakhanouskaya, Katsiaryna Y. (Experimental Biology and Biotechnology, 2018)
Objective of given research was to study the possibility using of iron caseinate as a feed additive for the prevention of iron deficiency anemia. In experiments on rats, it was established that after the intake of iron caseinate with a mass fraction of elemental iron of 3.65 %, the serum iron level increased significantly within 4 hours. In the model of iron deficiency anemia, after a single intake of iron caseinate at a dose of 2 g/kg, the number of erythrocytes, hemoglobin and hematocrit increased.
Keywords: iron; iron deficiency anemia; iron-protein compounds; casein; caseinate of iron